Ultra-tough injectable cytocompatible hydrogel for 3D cell culture and cartilage repair. Issue 9 (14th February 2018) - Zhao, Yanran; Li, Mengnan; Liu, Bingchuan; Xiang, Junfeng; Cui, Zhiyong; Qu, Xiaozhong; Qiu, Dong; Tian, Yun; Yang, Zhenzhong
Abstract : A high-performance hydrogel was synthesized by a facile dual dynamic crosslinking strategy that showed injectability, cytocompatibility, broadly tunable mechanical properties and the potential for repair of load-bearing tissues. Abstract : In this work, we developed a very facile strategy, i.e. dual dynamic crosslinking, to prepare a high performance injectable hydrogel. Poly(vinyl alcohol) (PVA) was crosslinked by 4-carboxyphenylboronic acid (CPBA) through the generation of borate bonding and ionic interaction to bridge the polymer chains in the presence of calcium ions. The dynamic gathering of CPBA could induce a self-reinforcing effect inside the hydrogel matrix, leading to high tensile and compressive moduli of the hydrogel over 1.0 MPa including the highest compressive modulus up to 5.6 MPa. Meanwhile, the mechanical properties of the hydrogel can be broadly and accurately tuned. And owing to the flexible PVA network, the hydrogel is ultra-tough, showing maximum tensile strain, tensile and compressive fracture energies up to 1600%, 600 kJ m −2 and 25 kJ m −2, respectively. Besides, the dynamic bonding overcomes the barriers to forming an injected strong hydrogel, e.g. to obtain a modulus and a fracture energy exceeding 1.0 MPa and 40 kJ m −2, by using a commercial dual-syringe kit under physiological conditions. Such a mild gelation procedure benefits the administration, 3D encapsulation and proliferation of cells of the hydrogels. The application of the PVA hydrogel was demonstrated by effective cartilage repair.